Network-based methods for gene function prediction. (4th March 2021) - Chen, Qingfeng; Li, Yongjie; Tan, Kai; Qiao, Yvlu; Pan, Shirui; Jiang, Taijiao; Chen, Yi-Ping Phoebe
Abstract: The rapid development of high-throughput technology has generated a large number of biological networks. Network-based methods are able to provide rich information for inferring gene function. This is composed of analyzing the topological characteristics of genes in related networks, integrating biological information, and considering data from different data sources. To promote network biology and related biotechnology research, this article provides a survey for the state of the art of advanced methods of network-based gene function prediction and discusses the potential challenges.